The Little Fly, the Big Impact: Drosophila in Green Chemistry Research - SAINI, RASHMI (RSYN Proceedings, 2025)
Designing chemical products and processes that minimize or eliminate the usage and production of hazardous materials is the goal of green chemistry principles. The fruit fly, Drosophila melanogaster, has emerged as a potent in-vivo model organism for evaluating the biological impact, environmental fate, and toxicity of novel, greener chemicals (e.g., catalysts, solvents, or degradable polymers) and the waste products they produce. The short lifespan, low maintenance costs, and conserved genetics with humans (about 75% of human illness genes have a fly ortholog) are the key reasons for the usefulness of Drosophila. It can quickly screen chemical libraries and have the risk profile and biocompatibility assessed of the chemicals created by green synthetic processes. Specifically, Drosophila models provide high-throughput toxicity screening, which makes use of basic metrics like as viability, lifespan, and fecundity to evaluate acute and chronic toxicity across different life stages. They link chemical structure to biological activity by using their transgenic lines to investigate chemical impacts on conserved biological pathways including neurotoxicity, mitochondrial function, or oxidative stress. They are utilized to evaluate the ecological safety and bioaccumulation or biotransformation potential of chemicals in organisms. Drosophila, plays a crucial role in validating the safety and success of green chemistry initiatives from the laboratory to industrial application as it offers a quick, ethical, and genetically tractable animal model system that accelerates the identification of sustainable and benign chemicals.